Interlingual And Intralingual Errorsof Writing Narrative Text Made By Junior High School And Senior High School Students - Pratiwi, Andini Puji; , Prof. Dr. Endang Fauziati, M. Hum; , Muamaroh, Ph.D (2015)
AndiniPujiPratiwi, S 200 130 044, 2015: "Interlingual and Intralingual Errors of Writing Narrative Text Made by Junior High School and Senior High School Students." The present study investigates the interference of L1 (Indonesian) into L2 (English) and the errors that occur due to the influence of TL (target language). The focus of the study is on the errors committed by these EFL learners in writing narrative text and emphasized on interlingual and intralingual errors. The objectives of the study are to investigate the errors committed by these EFL learners in order to find out; (1) the types of interlingual and intralingual errors in Junior High School and Senior High School, (2) frequencies of interlingual and intralingual errors in Junior High School and Senior High School, and (3) similarities and differences of interlingual and intralingual errors in Junior High School and Senior High School. To achieve these objectives, writing test was utilized in this study. The subjects of the study comprised 30 ninth grade school and 30 tenth grade school in Pekanbaru, Riau. The findings of the study suggest: (1) The types of interlingual and intralingual errors made by Junior High school and Senior High School divided into 2 levels, they are morphological level and syntactical level.(2) the frequent of interlingual errors in Junior High School 27,82% and 14,04% in Senior High School. The frequent of ofintralingual errors in Junior High School 72,17% and 85,96% in Senior High School, and (3) The similarities of interlingual and intralingual errors found in Junior High School and Senior High School are 2 types in morphological level and 2 types in syntactical level. The differences of interlingual and intralingual errors found in Junior High School and Senior High School are 1 type in morphological level and 11 types in syntactical level. Key word: error analysis, interlingual error, intralingual error, narrative text.